Pengaruh Edukasi Media Kartu “KABAR JASA” Terhadap Perilaku Jajanan Sehat Anak Kelas IV Dan V di SDN Karangtengah III Dan SDN Plembon Gunungkidul - Zahidah, Nuril Aini; Badi'ah, Atik; Suryani, Eko; Mendri, Ni Ketut (Poltekkes Kemenkes Yogyakarta, 2024)
Food and nutrition affect the growth and development of school-age children. Children's snacking behavior to fulfill their nutritional needs depends on the surrounding environment. Many foods that are usually sold are still unsafe because they contain several contaminants that don’t fulfull the requirements of healthy snacks. For this reason, it’s necessary to educate about the selection of healthy snacks to develop snacking behavior. The media used for education is picture card game media. This study aims to know the effect of